Fungsi Variasi Bahasa Jawa Pada Film Pendek 'Klalenan' Dalam YouTube Mugi Ketrock - Khasanah, Uswatun; Kusuma Anggraeni, Sri Prastiti (Sutasoma : Jurnal Sastra Jawa, 2024)
The film entitled, Klalenan by Mugi Ketrock with a duration of 12'.40" is a film in plain Ngoko language . This film was chosen by researchers because each conversation episode uses a variety of Ngoko innocent language and contains various language functions. The problems raised in this study are (1) How is the use of Ngoko innocent language in the conversation in The Short Film Klalenan?; (2) How does the Javanese language function in The Short Film Klalenan?. In line with the problem, the aim of the research is to describe the use of various ngoko lugu language in The Short Film Klalenan, as well as to describe the use refers to the theory developed by Michael Halliday, regarding the 7 functions of language in the life if Javanese society. The results obtained in the research are (1) Exposure to the use of Ngoko innocent language in evey conversation in every episode, and (2) the use of language functions in conversation including (1) Instrumental, (2) Regulatory, (3) Interactional, (4) Personal, (5) Heuristics, (6) Imagination, and repeesentational function.